The finish : the killing of Osama Bin Laden - Bowden, Mark (Atlantic Monthly Press : Distributed by Publishers Group West, 2012)
This work is a dramatic account of the hunt for and defeat of Osama bin Laden draws on unprecedented access to primary sources to trace how key decisions were made, revealing events from the perspectives of an adept President Obama and an increasingly despondent bin Laden. After masterminding the attacks of September 11, 2001, Osama bin Laden managed to vanish. Over the next ten years, as the author shows, America found that its war with al Qaeda, a scattered group of individuals who were almost impossible to track, demanded an innovative approach. Step by step, the author describes the development of a new tactical strategy to fight this war, the fusion of intel from various agencies and on the ground special ops. After thousands of special forces missions in Iraq and Afghanistan, the right weapon to go after bin Laden had finally evolved. By Spring 2011, intelligence pointed to a compound in Abbottabad; it was estimated that there was a 50/50 chance that Osama was there. The author shows how three strategies were mooted: a drone strike, a precision bombing, or an assault by Navy SEALs. In the end, the President had to make the final decision. It was time for the finish.